Absence of Neuronal Response Modulation with Familiarity in Perirhinal Cortex. (1st December 2018) - Baruchin, Liad J.; Ranson, Adam; Good, Mark; Crunelli, Vincenzo
Highlights: LFP responses to images could be observed in the mouse PRH – which can be used to translate to human studies. Under passive head-restrained viewing condition no familiarity response modulation could be observed in the PRH. When many novel complex images are presented familiarity modulation could be observed as upstream as V1. Abstract: The perirhinal cortex (PRH) is considered a crucial cortical area for familiarity memory and electrophysiological studies have reported the presence of visual familiarity encoding neurons in PRH. However, recent evidence has questioned the existence of these neurons. Here, we used a visual task in which head-restrained mice were passively exposed to oriented gratings or natural images. Evoked potentials and single-unit recordings showed evoked responses to novelty in V1 under some conditions. However, the PRH showed no response modulation with respect to familiarity under a variety of different conditions or retention delays. These results indicate that the PRH does not contribute to familiarity/novelty encoding using passively exposed visual stimuli.